PENGARUH EMOSI KEAGAMAAN TERHADAP KEDUDUKAN ANAK ANGKAT PADA MASYARAKAT BADUY MIGRAN (KASUS DESA CISIMEUT LEBAK BANTEN) - Ade Lilis Suryani; Yuwono Prianto (Jurnal Hukum Adigama, 2019)
Children are one of the gifts of the Almighty God as a mandate and must be protected, loved and guaranteed for all their needs. The child referred to here is a legitimate child, an extramarital child and adopted child. The position of adopted children in Indonesia is governed by positive law, Islamic law, and customary law. In customary law each indigenous community in various regions has its own character and mechanism. As in Kasud in the village of Cisimeut Lebak, Banten, that is in the indigenous Baduy community. In the results of the study, it was pointed out that local customary law was still more enforced than religious norms. This is evidenced by the discovery of the Baduy migrants from the Baduy tribe due to conversion. While the majority of the beliefs of the Baduy people are Sundanese wiwitan. With the development of the times, technology and community interaction became one of the factors supporting the influence of the religious emotions of the Baduy community.